Pemberdayaan Masyarakat Lansia Dalam Kegiatan Sekolah Lansia di Kecamatan Bandungan - Chorinta Wulan Athaya; Bagus Kisworo (EduInovasi: Journal of Basic Educational Studies, 2025)
The increasing number of elderly people is a challenge for all groups. This can become a problem if not addressed immediately. To address these problems, elderly schools are a solution in increasing the capacity of the elderly. This study aims to describe the empowerment process that occurs at the Pancasila Elderly School in Bandungan District. The research method uses descriptive qualitative methods that focus on three stages of the empowerment process: awareness, transformation, and capacity building. Furthermore, the empowerment outcomes focus on cognitive, psychomotor, and independence improvements. Data collection techniques include observation, interviews, and documentation. Analysis techniques used include data collection, data reduction, data presentation, and conclusion drawing. The results show that the empowerment of the elderly community through elderly school activities is running well by implementing a gradual empowerment process. At the awareness stage, the Elderly School is able to raise awareness among the elderly to join the elderly school program through various efforts. The transformation stage is marked by increased participation of the elderly in attending the elderly school. Tutors provide material on health to ensure the success of this stage. In the final stage, the capacity building stage, the elderly experience increased capabilities, especially in the health sector, enabling them to live independently without requiring assistance from family and the community. Improvement in the elderly is characterized by cognitive improvement, namely the growth of the elderly's knowledge and ability to think. Furthermore, psychomotor development in the elderly develops through exercise, increasing the elderly's ability to take responsibility for themselves, thus supporting them in achieving independence in their lives.